Global value chains, employment, and wage inequality: A study of Indian manufacturing - Subash Sasidharan; Shandre Mugan Thangavelu; Renjith Ramachandran (Asian Development Bank Institute (ADBI), 2024)
Using plant-level data from the Annual Survey of Industries, this study presents an empirical analysis of the effects of global value chains (GVCs) on employment and wage premiums in the Indian manufacturing sector. We emphasize the GVC's impact on three labor market variables: (i) employment, (ii) the wage premium among skilled, unskilled, male, and female workers, and (iii) wage inequality based on skill and gender. The analysis in the paper consists of four sub-categories of workers: skilled, unskilled, male, and female workers. We find that participation in GVCs is positively associated with employment and wages. We also find that these effects are more pronounced for skilled workers and that GVC participation significantly increases wage gaps between skilled and unskilled workers. There are several policy implications from the study: (i) the skills of workers should be improved through training and re-tooling, (ii) a strong monitoring framework on the dynamics of the labor market should be developed in terms of unbundling the effects of the GVC, and (iii) strong labor market institutions need to be developed to create more forward-looking policies that will increase the "future skills" of domestic workers.
Keywords: F16; F61; 330; GVC; employment; wage inequality; manufacturing; India